Pemanfaatan Data Penginderaan Jauh dan Sistim Informasi Geografis Untuk Identifikasi Perkembangan Lahan Terbangun pada Wilayah Rawan Gempa Bumi di Kota Ambon - Philia Christi Latue; Heinrich Rakuasa (Yayasan Literasi Sains Indonesia, 2023)
Earthquakes are natural disasters that often occur in Indonesia, including in Ambon City which is located in an earthquake-prone area. This research aims to identify the development of built-up land in earthquake-prone areas in Ambon City by utilizing remote sensing data and geographic information systems. This research uses data on built-up land in Ambon City in 2019 and 2023 as well as earthquake hazard maps. The results show that built-up land in Ambon City in 2013-2023 experienced a significant increase in area from 4,718.17 ha in 2013 increasing in area in 2023 to 6,762.57 ha. The area of built-up land located in earthquake-prone areas in Ambon City has a relationship that is directly proportional to the year of development of built-up land. So that as the year increases, the area of built-up land located in earthquake-prone areas also increases. The results of this research are expected to serve as a basis for developing policies and mitigation strategies aimed at the sustainability of the Ambon City area amid the existing earthquake threat.